Sistem Informasi Penjualan Berbasis Web Pada Pucabranded.Store - Putri, Fetty Ade; Muhatri, Muhatri; Doni, Rahmad; Hulu , Dafid Putra (CV. Information Technology Training Center - Indonesia (ITTC), 2021)
Pucabranded.store is a business engaged in the sale of quality used branded shoes, which is located at Jalan Deli Tua, Medan. The current problem at the pucabranded.store store is in selling, promoting and ordering still manually, this is less effective because there is no detailed information about shoes on pucabranded.store for consumers. The ordering process that is currently running on t pucabranded.store is still using via Instagram or coming directly to the place, it is still not efficient. Recording and checking of transaction data, customer data, goods data, is still done manually in written document archives, data loss is still likely to be vulnerable to occur. The method used here is more directed to the research process with the Waterfall Method. In the construction of a system like this, to make it easier to sell, make transactions easily, make it easier for buyers to purchase goods online if they are far away, increase income and expand sales promotions on pucabranded.store.